JENIS-JENIS PEMBELAJARAN JARAK JAUH BERBASIS TEKNOLOGI INFORMASI UNTUK PARA PENGUSAHA - Meiyanto Eko Sulistyo (Jurusan Teknik Informatika, 2012)
Distance learning is a learning strategy in which students and faculty interact via theInternet and delivered through video and audio conferencing, collaboration between students,and participate in a synchronous or asynchronous instruction.Types of distance learning basedon information technology which is suitable for businesses, e-learning and instant messaging.Instant Messaging can save the cost of purchasing a computer server and leases officebuildings, it will give birth to the concept of e-office (electronic-office).Distance learning basedon information technology very useful for entrepreneurs, because it can save the cost oftraining.Keywords: distance learning, e-learning, employers, instant messaging, informationtechnology